Comparison of susceptibility of Neisseria meningitidis to sodium sulphadiazine and sodium fusidate in vitro. Issue 4 (April 1978) - Miles, R S; Moyes, A
Abstract : Out of 100 strains of meningococci examined 62 were resistant to 1 mg/l or more of sodium sulphadiazine, including 82% of group W135 strains and 69% of group B strains. All strains were sensitive in vitro to 0.5 mg/l of sodium fusidate. Sodium fusidate should be considered as a chemoprophylactic agent for those who may be at risk of meningococcal disease.